Habitat associations of marine predators in the northern California Current during the low productivity downwelling season - Bliss, Laura M.; Zamon, Jeannette E.; Davoren, Gail K.; Hanson, M. Bradley; Noren, Dawn P.; Emmons, Candice; Holt, Marla M. (Frontiers in Marine Science, 2024)
Eastern Boundary Upwelling Systems are some of the most productive marine ecosystems in the world. Little is known about habitat associations and spatial distributions of marine predators during seasonal periods of low-productivity because there are few at-sea surveys during this period. During low productivity or prey scarcity, predators consuming similar prey in the same time and space may compete for limited resources, or they may avoid competition by exploiting different habitats or occupying separate spaces (i.e. niche partitioning). In this study, we examined habitat associations and niche partitioning of marine predators during the low productivity winter downwelling season of the northern California Current Ecosystem (CCE). Seabird and marine mammal counts were continuously collected during systematic at-sea surveys during February–March/April in the northern California Current across four years (2006, 2008, 2009, and 2012). We examined seabird and marine mammal distributions in relation to seven habitat characteristics (i.e., sea surface temperature (°C), salinity, depth (m), seafloor slope (%), distance from shore (km), and distance from the 100 m and 200 m isobaths (km)). We used a non-parametric multivariate analysis (i.e. canonical correspondence analysis (CCA)) to quantify species’ habitat associations and directional distribution ellipses to explore overlap in species core winter habitat. Results show 49 seabird and ten marine mammal species inhabit the CCE during this low productivity period, including endangered southern resident killer whales (Orcinus orca). Seabirds and marine mammals exhibited significant but low overlap in habitat associations (i.e. weak niche partitioning) and similar habitat associations to summer studies. We also found that some species with similar foraging strategies showed asymmetrical spatial range overlap (i.e. common murre (Uria aalge) and parakeet auklet (Aethia psittacula), which may mean that expected increased competition due to climate change can negatively affect some species more than others. Given that climate change is leading to increased frequencies, intensities, and durations of marine heat waves during winter months, addressing the winter ecology knowledge gap will be important to understanding how climate change is going to affect species that reside in or migrate through the northern California Current during the low productivity downwelling season.